Intraspecific Variability of Floral Nectar Volume and Composition in Rapeseed (Brassica napus L. var. oleifera) - Bertazzini, Michele; Forlani, Giuseppe (Frontiers in Plant Science, 2016)
Numerous angiosperms rely on pollinators to ensure efficient flower fertilization, offering a reward consisting of nourishing nectars produced by specialized floral cells, known as nectaries. Nectar components are believed to derive from phloem sap that is enzymatically processed and transformed within nectaries. An increasing body of evidence suggests that nectar composition, mainly amino acids, may influence pollinator attraction and fidelity. This notwithstanding, little is known about the range of natural variability in nectar content for crop species. Sugar and amino acid composition of nectar harvested from field-grown plants at the 63 to 65 phenological stage was determined for a set of 44 winter genotypes of rapeseed, a bee-pollinated crop. Significant differences were found for solute concentrations, and an even higher variability was evident for nectar volumes, resulting in striking differences when results were expressed on a single flower basis. The comparison of nectar and phloem sap from a subset of 8 varieties pointed out qualitative and quantitative diversities with respect to both sugars and amino acids. Notably, amino acid concentration in phloem sap was up to one hundred times higher than in nectar. Phloem sap showed a much more uniform composition, suggesting that nectar variability depends mainly on nectary metabolism. A better understanding of the basis of nectar production would allow an improvement of seed set efficiency, as well as hive management and honey production.